Itinerários, práticas e significações do sexo tarifado entre homens - Hamann, Cristiano (2016)
The present study has the aim to explore the significance and meanings attributed to the men’s prostitution in Porto Alegre, Rio Grande do Sul. For this, a survey by two collection processes linked and inseparable data was performed: The first being an ethnographic incursion inspiration for the men’s prostitution places in the city, and the second a series of interviews with men who engage in prostitution, business managers and promoters of these places. The interviews and ethnographic experiences in the field were fed back, looking for understanding and rebuilding a usual route of men who prostitute in Porto Alegre. Through a glance at tuning of Gender Studies, adhering to an intersectional perspective, this research gave rise to an understanding of how the negotiations on tariffed sex are crossed by markers of difference that place certain men, contextually, in higher positions or less possibility of articulation. In addition, it seeks to reflect on the formation of communities of practice in this context, a phenomenon that includes interactions among men who prostitute themselves, establishing managerial into prostitution and clients.